Vultron : towards secure smart contracts -- a runtime monitoring approach - Yang, Xuan (2019)
Ethereum smart contracts are paving their way into the future of commerce and high stakes are placed upon the correct implementation of their specifications. However, in the history of Ethereum, several vulnerabilities have been exploited which compromised the trust and effectiveness of smart contracts. Errors in executable specification languages are especially challenging to detect using a static approach. Therefore, a dynamic runtime monitoring approach is often preferred. The proposed approach, Vultron, a generalised solution which is not limited in its capabilities, can proactively detect vulnerabilities during runtime, and pre-emptively alter the function execution.